2005
DOI: 10.1038/sj.jhh.1001915
|View full text |Cite
|
Sign up to set email alerts
|

Maternal age in pregnancy and offspring blood pressure in childhood in the Avon Longitudinal Study of Parents and Children (ALSPAC)

Abstract: Associations between maternal age in pregnancy and offspring blood pressure (BP) at age 7 1 2 were investigated in 7623 singletons from the Avon Longitudinal Study of Parents and Children (ALSPAC). In models adjusted for age and sex there was an inverse relationship between maternal age and BP in children: b ¼ À0.06 mmHg per year of maternal age (95% CI À0.10 to À0.01, P ¼ 0.02) for systolic BP and b ¼ À0.04 (95% CI À0.07 to À0.01, P ¼ 0.02) for diastolic BP.However, this association disappeared after adjustme… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

1
20
1

Year Published

2007
2007
2022
2022

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 13 publications
(22 citation statements)
references
References 25 publications
1
20
1
Order By: Relevance
“…That the effect of infant diet on child BP was barely attenuated by adjustment for both birth weight and current child body size may have indicated that the observed association between diet and BP was unlikely to be explained solely in terms of either fetal growth restriction or catch-up growth. Nor does the effect appear to be dependent on prenatal factors, such as maternal characteristics or sociodemographic factors, which is an observation consistent with other studies (14,41,42). Because the final regression model (4) showed that current body weight influenced systolic BP and attenuated the effect of early diet on BP, our results also highlighted that the tracking of diet might be one mechanisms through which current body weight influences BP.…”
Section: Discussionsupporting
confidence: 85%
See 1 more Smart Citation
“…That the effect of infant diet on child BP was barely attenuated by adjustment for both birth weight and current child body size may have indicated that the observed association between diet and BP was unlikely to be explained solely in terms of either fetal growth restriction or catch-up growth. Nor does the effect appear to be dependent on prenatal factors, such as maternal characteristics or sociodemographic factors, which is an observation consistent with other studies (14,41,42). Because the final regression model (4) showed that current body weight influenced systolic BP and attenuated the effect of early diet on BP, our results also highlighted that the tracking of diet might be one mechanisms through which current body weight influences BP.…”
Section: Discussionsupporting
confidence: 85%
“…Birth weight and postnatal weight gain have been associated with later BP in some studies (41). However, the association we observed between the less-healthy transition diet and child BP persisted after adjustment for body size, both at birth and at measurement of BP.…”
Section: Discussioncontrasting
confidence: 48%
“…Two studies reported positive associations between maternal age and offspring BP (27,55). A third reported differing effects for female and male offspring (56) and the fourth study reported an inverse association between maternal age at childbirth and offspring BP that disappeared after adjusting for confounders (57).…”
Section: Maternal Agementioning
confidence: 99%
“…18 In humans, it is reasonably well established that offspring of older mothers tend to be taller [19][20][21] and have a slightly higher risk of childhood type 1 diabetes (5% per 5-year increase in mother's age, according to a meta-analysis of 30 studies). 22 However, the evidence linking mother's age at delivery with offspring blood pressure, 19,[23][24][25][26] glucose metabolism, 20,27,28 and, especially, body mass index (BMI) [19][20][21][29][30][31][32][33][34] is mixed.…”
mentioning
confidence: 99%